Direct PCR Improves the Recovery of DNA from Various Substrates1. Issue 6 (12th August 2015) - Templeton, Jennifer E. L.; Taylor, Duncan; Handt, Oliva; Skuza, Pawel; Linacre, Adrian
Abstract: This study reports on the comparison of a standard extraction process with the direct PCR approach of processing low‐level DNA swabs typical in forensic investigations. Varying concentrations of control DNA were deposited onto three commonly encountered substrates, brass, plastic, and glass, left to dry, and swabbed using premoistened DNA‐free nylon FLOQswabs ™ . Swabs ( n  = 90) were either processed using the DNA IQ ™ kit or, for direct PCR, swab fibers (~2 mm 2 ) were added directly to the PCR with no prior extraction. A significant increase in the height of the alleles ( p  < 0.005) was observed when using the direct PCR approach over the extraction methodology when controlling for surface type and mass of DNA deposited. The findings indicate the potential use of direct PCR for increasing the PCR product obtained from low‐template DNA samples in addition to minimizing contamination and saving resources.